Analyzing the prevalence of sports-related terms among the web sites of global corporations - Scharl, A.; Neale, L.; Murphy, J. (International Journal of Computer Science in Sport, 2004)
This research investigates the prevalence of sports-related terms among the Web sites of the world`s leading companies, the Fortune Global 500. An automated process copied about four gigabytes of textual data, around 70 million words, from their sites. The subsequent analysis revealed regional and industry differences in the distribution of sports-related terms, the popularity of tennis stars and few references to sports stars, especially in Asia.